Moderate-intensity Exercise Decreases Cortisol Response in Overweight Adolescent Women - Yasep Setiakarnawijaya; Widiastuti Widiastuti; Muhamad Syamsul Taufik; Kuswahyudi Kuswahyudi; Awaluddin Awaluddin; Ibnu Sina; Andi Hasriadi Hasyim; Hasyim Hasyim; Abdul Hafidz; Nur Ahmad Muharram (Physical Education Theory and Methodology, 2022)
The study purpose was to demonstrate the effect of moderate-intensity exercise on reducing cortisol levels in overweight adolescent women.